Intravenous Tigecycline Facilitates Cure of Severe Clostridium difficile Infection (CDI) After Failure of Standard Therapy: A Case Report and Literature Review of Tigecycline Use in CDI. (12th May 2016) - Navalkele, Bhagyashri D.; Lerner, Stephen A.
Abstract: Standard treatment for severe Clostridium difficile infection (CDI) is oral vancomycin with metronidazole. After failure of this standard regimen, treatment becomes challenging. A young woman treated for septic shock developed CDI. Standard treatment failed and she was ineligible for fecal transplant. Addition of tigecycline to her regimen resulted in cure.